The Evolution of Modern Behaviour and its Implications for Maritime Dispersal During the Palaeolithic. Issue 4 (12th May 2015) - Leppard, Thomas P.
Abstract : Oceans and seas are more frequently thought to have been barriers to than enablers of movement for archaic hominins. This interpretation has been challenged by a revisionist model which suggests that bodies of water facilitated the dispersal of pre-moderns. This paper addresses the revisionist model by defining maritime dispersal as a series of cognitive and organizational problems, the capacity to solve which must have arisen during the evolution of Homo . The central question posed is: knowing the type of social and cognitive configuration necessary for strategic maritime dispersal, and knowing the social and cognitive capacities of hominin species implied in the revisionist dispersal model, how likely is it that such species possessed the capacity to undertake purposive maritime colonization? Available data suggest that the evolution of modern cognitive architecture during the Late Pleistocene correlates positively with increasing evidence for maritime dispersal in the Upper Palaeolithic, and that behavioural modernity is implicated in the appearance of strategic maritime dispersal in Homo. Consequently, it is likely that deliberate trans-oceanic seagoing is restricted to Anatomically Modern Humans, and possibly Neanderthals.